In the Court of the Rainmaker: The Willing Deviant in Longana, Vanuatu - Rodman, William L.; Rodman, Margaret C. (Anthropologica, 2022)
In the district of Longana in Vanuatu the weather is not merely a physical but a social phenomenon. Rainmakers are responsible for gentle rains which benefit the crops and the community, but they can also cause continual downpours and floods. An examination of ethnographic literature from Oceania and elsewhere reveals relatively few cases where rainmakers are said to act in a deviant fashion. In one particular and unprecedented case which the authors examine, an individual confessed to small-scale acts of deviance in the past, when accused of responsibility for a protracted period of rain. The implications of that confession both for the individual and his community are examined, and some conclusions are drawn about differences between the ways Longanans and Westerners classify and treat deviant actions.